Analisis Efisiensi Kurikulum Program Studi Teknik Industri Universitas Kristen Petra - Garry Geraldy; Iwan Halim Sahputra; Karina Agustin (Jurnal Titra, 2021)
The curriculum of the Petra Christian University Industrial Engineering Study Program is always updated every four years to keep up with the times, especially in science and technology. However, the evaluation carried out in the curriculum changes did not include the analysis of efficiency and student study results. The curriculum that evaluated in this final project are the curriculum in 2007, 2012, and 2016 with student data used are class 2007, 2012 and 2016. Curriculum evaluation is analyzed using the efficiency measurement method. In addition to efficiency calculations and analysis, this study also looks for the influence between curriculum and majors on GPA by using One-Way ANOVA, Kruskall Wallis, Paired T-Test and Wilcoxon Signed Rank tests. The results obtained indicate that the curriculum changes made by Industrial Engineering are more efficient. Curriculum efficiency has a significant effect on the final GPA and the length of time students graduate. In addition, there is an increase in the final GPA of students compared to the GPA until semester 5, before determining the majors.